Difusi Inovasi Aplikasi Identitas Kependudukan Digital (IKD) Dinas Kependudukan dan Pencatatan Sipil Kota Kendal (Lembaga Pengembangan Kinerja Dosen, 2026)
The Digital Population Identity (IKD) constitutes a pivotal government innovation aimed at transforming public services, yet its widespread adoption is impeded by disparities in digital literacy and inherent technical constraints. This community engagement activity, integrated with a participatory internship scheme, concentrates on analyzing and supporting the innovation diffusion trajectory executed by the Population and Civil Registration Department (Disdukcapil) of Kendal City. The adopted methodology employs a Participatory Action approach, strategically combined with a mobile service paradigm (jemput bola) across three designated urban villages: Langenharjo, Kebondalem, and Karangsari. Core interventions involved intensive, interpersonal socialization sessions and customized technical support for account activation. The assessment findings robustly suggest that the